Proceedings of the 3rd Asian Education Symposium (AES 2018) 2019
DOI: 10.2991/aes-18.2019.30
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Teacher's Commitment to Organizations through the Development of Organizational Culture and Situational Leadership

Abstract: The purpose of this research is to seek efforts to increase the teacher's commitment to the organization through the development of organizational culture and situational leadership. The study was conducted using correlation statistical methods to determine whether other variables, namely organizational culture and situational leadership, had a positive relationship with the teacher's commitment to the organization. Data analysis is performed using the Sitorem method to make recommendations and determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Collaborative culture and school structures could be influenced by school leadership and could jointly impact teaching and learning ( Lomos et al, 2011 ; Camburn and Han, 2017 ). Previous studies have proved that collaborative culture built by school leaders could improve teachers’ professional development, job satisfaction, and commitment ( Eaker and DuFour, 2009 ; Hong et al, 2016 ; Olson, 2019 ; Suhardi et al, 2019 ). For example, Olson (2019) found that school leadership could positively influence teacher commitment by building a collaborative culture.…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative culture and school structures could be influenced by school leadership and could jointly impact teaching and learning ( Lomos et al, 2011 ; Camburn and Han, 2017 ). Previous studies have proved that collaborative culture built by school leaders could improve teachers’ professional development, job satisfaction, and commitment ( Eaker and DuFour, 2009 ; Hong et al, 2016 ; Olson, 2019 ; Suhardi et al, 2019 ). For example, Olson (2019) found that school leadership could positively influence teacher commitment by building a collaborative culture.…”
Section: Introductionmentioning
confidence: 99%